Polja. La fecondità carsica del tema educativo nel lavoro di Fulvio Papi - Madrussan, Elena (Materiali di estetica. Terza serie (Online), 2023)
Education as a philosophical issue, as a personal experience and as a cultural expression of our time has run through Fulvio Papi’s work longitudinally. The works dedicated explicitly to this subject have been interwoven with those of witnessing, on several occasions, the cultural history of the School of Milan, without neglecting the ‘autobiographical’texts, where the memories of school, teachers, schoolmates and the experiences that made them eloquent find their place and ever new meaning. There is, however, also a more subtle focus on education, which emerges in Papi’s work as do the Karst landscapes, close to his beloved Trieste. Taking this scenario as an imagine of meaning, it is also possible to find hidden strata and fertile ground in other texts, where one’s own formation is anchored in the ability to emerge as a culturally aware and socially responsible self. In particular, The Luxury and the Catastrophe (2006) stands out for its formative intensity. Here, the ‘feeling of life’ of becoming a subject is grafted into the ethical-social dimension in at least two ways. The first way, argumentative, concerns the ego’s relationship with reality, where catastrophe is grasped as the current world-form and luxury corresponds to the form of thought from which it is impossible to separate oneself, even when it risks sterilising understanding. The second, methodological mode identifies in the processes of adhesion and differentiation of the ego from the self the only real possibility of coming to terms with a relationship with the world that is inexorably partial and lacking. Just like poljas, Papi’s books are fields (the world-forms) that are always fertile because they are irrigated by streams of water or hidden aquifers (the subjectivities) and surrounded by rocky outcrops (the luxury of thought) that protect and bound them. To recognise them, one must go deep.